Meningkatkan Kemampuan Berkomunikasi Anak melalui Permainan Kartu Kata Bergambar pada Kelompok B TK PKK Terpadu Mayang Nira Selong Kecamatan Selong Tahun Pelajaran 2020/2021 - Mahnim, Mahnim (Lembaga Yasin AlSys, 2021)
This research will be carried out in group B of the Integrated PKK Kindergarten Mayang Nira Selong, Selong District, East Lombok Regency, for the 2020/2021 academic year. This classroom action research is planned to be carried out for 4 months from January to April. This Classroom Action Research is carried out in 2 cycles, each cycle is carried out in 3 meetings in 2 weeks. So in 2 cycles will be carried out for 4 weeks. Each meeting is held in 2 hours of lessons with 30 minutes of each lesson. The application of picture word card games can improve activities and communication skills through picture word card game activities for children in group B of the Integrated PKK Kindergarten Mayang Nira Selong. This increase can be seen from the acquisition of children's activity scores, teacher activities and class average scores as well as classical completeness levels in each cycle which have increased in cycle I and cycle II.